1996
DOI: 10.1136/oem.53.9.636
|View full text |Cite
|
Sign up to set email alerts
|

Work related risk factors for musculoskeletal complaints in the nursing profession: results of a questionnaire survey.

Abstract: Objectives-To determine the prevalence of musculoskeletal complaints of the back, arms or neck, and legs among nurses, and to investigate the relation between these complaints and various work related and personal variables. Methods-A questionnaire survey was carried out in four nursing homes in The Netherlands. Results-The response was 95% and resulted in 846 completed questionnaires. It was found that a large proportion of the subjects regularly had back complaints (36%) but also had arm or neck (30%) and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
128
5
18

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(166 citation statements)
references
References 21 publications
15
128
5
18
Order By: Relevance
“…In contrast, it was higher than other research conducted among Australian nursing home employees (20.7%) (22), South Korean foundry workers (13.7%) (17) and Taiwanese palliative care staff (8.0%) (23). The prevalence of arm localised MSD reported during the present research was lower than 2 previous nursing home studies conducted in Holland (30.4 and 35%) (10,9) in addition to the aforementioned South Korean hairdresser study (28.5%) (19). However, it was higher than that of Japanese hospital nurses (18.6%) (1) and South Korean foundry workers (13.7%) (17).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast, it was higher than other research conducted among Australian nursing home employees (20.7%) (22), South Korean foundry workers (13.7%) (17) and Taiwanese palliative care staff (8.0%) (23). The prevalence of arm localised MSD reported during the present research was lower than 2 previous nursing home studies conducted in Holland (30.4 and 35%) (10,9) in addition to the aforementioned South Korean hairdresser study (28.5%) (19). However, it was higher than that of Japanese hospital nurses (18.6%) (1) and South Korean foundry workers (13.7%) (17).…”
Section: Discussioncontrasting
confidence: 89%
“…Their activities are known to alternate rapidly and be of short duration (9). Working under time pressures with limited ability to take rest breaks are also common features among this demographic (10). Physical stress from providing round-the-clock assistance to nursing home patients may be a causal factor in workplace injury and illness (11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to this research, another study of nursing workers also found an association between work time and MSD in neck and arms, and lack of this association for low back MSD, a finding that is linked with the healthy worker effect (18) . It is suggested that workers with pain in low back region tend to leave the nursing profession earlier, due to these complaints.…”
Section: Variables Frequencysupporting
confidence: 74%
“…It is suggested that workers with pain in low back region tend to leave the nursing profession earlier, due to these complaints. Abandonment due to pain in neck and arms is possibly less common because those are less disqualifying (18) . Yet, some authors (4,19) raise the hypothesis that no association between MSD in low back and work time is due to better coping strategies for physical loads, developed by more experienced professionals.…”
Section: Variables Frequencymentioning
confidence: 99%
“…Among work-related risk factors, the physical events like lifting, awkward postures and stooping (Engels et al 1996;Schenk et al 2007), are considered the most important sources of this kind of disorders. Moreover the study of biomechanical and psychosocial factors low back pain-related shows a great influence in return to nursing activities determining different levels of disability (Denis et al 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 4 2007).…”
Section: Introductionmentioning
confidence: 99%